Self-Determination in Indigenous Health: A Comprehensive Perspective (Fourth World Journal, 2025)
Indigenous health disparities are devastating. Indigenous health research has focused mainly on biomedical approaches. Prevailing evidence indicates that models that integrate concepts of biomedical care and traditional healing are better suited to improvehealth outcomes among Indigenous groups. In this article the author focuses on holistic approaches to health as initiated by self-determined indigenous health movements. The paper suggests comprehensive frameworks to tackle Indigenous health issues in their full complexity. Frameworks that take into consideration a combination of social, cultural, economic, environmental and political factors to influence health status. The author also discusses traditional medicine and self-determination in the U.S. system, recommends international policy and points to future action and research that may remedy deficits inindigenous health.